Foundation pit muck alkali-activated mortar as well as preparation method and application thereof
The alkali-exciting mortar of foundation pit slag and slag is prepared through alkali-exciting reactions of foundation pit slag and slag, which solves the problems of high solid waste treatment costs and carbon emissions, and realizes the preparation of polymer mortar with high durability and early strength. Promote the high-value utilization of solid waste and the development of a green economy.
Patent Information
- Application Number
- CN202411448019.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-17
AI Technical Summary
In the prior art, solid waste such as foundation pit discarded soil and slag have problems such as high cost, serious pollution and large resource occupation, and the production of traditional cement mortar requires high temperature calcination to cause carbon emissions.
Foundation pit slag, slag and alkali exciters (water glass and sodium hydroxide) are used to prepare foundation pit slag alkali excitation mortar. The polymer mortar is formed through alkali excitation reaction, which is used in building materials, and the foundation pit slag is omitted. Transport and landfill steps to reduce land occupation and reduce production costs and carbon emissions.
The preparation of polymer mortar with high durability and early strength has been achieved, which has reduced the demand for natural resources in the construction industry, promoted the high-value utilization of solid waste and the development of a green economy, and reduced production costs and carbon emissions.
Smart Images

Figure CN119320259A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a foundation pit slag alkali-activated mortar and a preparation method and application thereof. Background Art
[0002] In recent years, my country's urbanization level has increased rapidly, infrastructure construction has flourished, and the development of land space has become increasingly important. However, the engineering waste soil generated during the construction process, especially the foundation pit waste soil, has become the main component of domestic construction waste. The amount of these waste soils is huge, and long-distance transportation will not only lead to a large amount of carbon emissions, but traditional disposal methods such as landfill will also occupy a large amount of land resources.
[0003] Slag is a common industrial solid waste with high volcanic ash activity. It can be used as an alkali-activated material to form geopolymers through the action of alkali activators. Geopolymers are high-quality building materials with excellent mechanical properties and durability.
[0004] Existing patents CN108046669A, CN111393117A, CN110510966A, and CN115215597A all disclose different methods for preparing geopolymers, all of which use engineering waste soil as the main raw material, such as shield slag, and alkali activators. Therefore, alkali-activated mortars suitable for geopolymer construction products have great future application potential. Summary of the invention
[0005] The purpose of the present invention is to provide a foundation pit slag alkali-activated mortar and its preparation method and application in order to overcome the existing technical problems such as large solid waste inventory, high cost of building materials products, serious pollution, etc.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] One of the technical solutions of the present invention is to provide a foundation pit slag alkali activated mortar, which is composed of the following raw materials in parts by weight:
[0008] Foundation pit soil, 100 parts; slag, 25-80 parts; alkali activator, 5-28 parts; water, 40-80 parts;
[0009] Wherein, the alkaline activator is composed of 4 to 14 parts of water glass and 1 to 4 parts of sodium hydroxide.
[0010] In some specific implementations, the particle size of the foundation pit debris is greater than 0 mm and less than 2.5 mm, and the moisture content is less than or equal to 4%.
[0011] In some specific embodiments, the particle size of the slag is greater than 0 mm and less than 0.075 mm.
[0012] In some specific embodiments, the water glass modulus of the water glass is 2.5-3.5.
[0013] In some specific embodiments, the mass of the foundation pit soil is m1, the water content is w1, and the mass of the slag is m k , the mass of sodium hydroxide is m g , the mass of water glass is m y , the soil-binder ratio satisfies the following relationship:
[0014]
[0015] In some specific embodiments, the mass of the foundation pit soil is m1, the moisture content is w1, and the mass of the added water is m s , the mass of slag is m k , the mass of sodium hydroxide is m g , the mass of water glass is m y , the liquid-to-solid ratio satisfies the following relationship:
[0016]
[0017] In some specific embodiments, the compressive strength of the foundation pit debris alkali-activated mortar is greater than 5 MPa, the softening coefficient is ≥0.9, and the water absorption rate is ≤2%.
[0018] In some specific embodiments, the 3-day compressive strength of the foundation pit slag alkali-activated mortar is greater than 5 MPa, and the 7-day compressive strength is greater than 10 MPa, and it has early strength, while the 7-day strength of general cement-solidified soil is about 2-4 MPa.
[0019] The foundation pit slag alkali-activated mortar has a softening coefficient of ≥0.9 and a water absorption rate of ≤2%, so it is more durable than general cement-solidified soil.
[0020] The second technical solution of the present invention is to provide a method for preparing foundation pit slag alkali activated mortar as described in one of the above technical solutions, and the specific steps are as follows:
[0021] Add slag, alkali activator and water to the foundation pit debris according to parts by mass and stir until uniform to obtain the foundation pit debris alkali activated mortar.
[0022] In some specific embodiments, slag is first added to the foundation pit debris by mass, stirred until uniform, and then an alkali activator and water are added and stirred until uniform. When the fluidity reaches 170 mm, foundation pit debris alkali-activated mortar is obtained.
[0023] The third technical solution of the present invention is to provide an application of the foundation pit residue alkali-activated mortar as described in one of the above technical solutions, and the application of the foundation pit residue alkali-activated mortar in building materials products.
[0024] In some specific embodiments, the building material product is one or more of standard bricks, pavement bricks, garden landscape retaining stones, curbstones, grass bricks, slope protection bricks, prefabricated drainage ditches, and retaining wall blocks.
[0025] The third technical solution of the present invention is to provide an application of the foundation pit residue alkali-activated mortar as described in one of the above technical solutions, and the application of the foundation pit residue alkali-activated mortar in emergency repair building materials product engineering.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] (1) The present invention provides an alkali-activated mortar of foundation pit debris with early strength and high durability. The mortar adopts waste soil generated in the construction process, such as foundation pit debris and industrial by-products such as slag, as raw materials, omitting the steps of transportation and landfill of foundation pit debris. The mortar is more efficient and energy-efficient, and saves precious land resources. It not only promotes the high-value utilization of construction solid waste, but also reduces the demand for natural resources in the construction industry, and promotes the development of the green economy.
[0028] (2) The present invention adopts the alkali excitation principle to prepare geopolymer mortar. Compared with traditional cement mortar, it does not have the additional carbon dioxide produced by calcining limestone, does not require high-temperature calcination, is more energy-saving and low-carbon, and optimizes the performance of traditional cement mortar while also reducing production costs, which is in line with the green economy, thus taking an important step in improving the environmental sustainability of building materials.
[0029] (3) The present invention is based on the alkali-activated reaction between slag and alkali activator (water glass, sodium hydroxide), which produces reaction products such as CASH and CSH. The reaction products are bonded to each other, and then bond the slag particles. The slag acts as a filling material in the system, filling the pores and improving the density. Since the alkali-activated reaction is faster than the traditional cement hydration reaction, the prepared foundation pit slag alkali-activated mortar has the characteristics of early setting and rapid strength, and can be applied to practical engineering fields such as emergency repair. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The present invention is a flow chart of the method for preparing foundation pit slag alkali-activated mortar. DETAILED DESCRIPTION
[0031] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0032] In the following examples and comparative examples, unless otherwise specified, raw materials or processing techniques are conventional commercially available raw materials or conventional processing techniques in the art.
[0033] A method for preparing foundation pit slag alkali activated mortar, the specific process is shown in Figure 1 , including the following steps:
[0034] (1) Take the foundation pit debris raw material and crush it to obtain the foundation pit debris with a particle size of less than 2.5 mm.
[0035] (2) Test the initial moisture content of the foundation pit soil. If the moisture content is greater than 4%, the foundation pit soil needs to be aired first. Test the moisture content again. If it is still greater than 4%, repeat the above steps until the moisture content is less than 4%, which is qualified.
[0036] (3) After calculating the mix ratio according to 1.00 < soil-binder ratio < 3.50, 0.3 < liquid-solid ratio < 0.6, start preparing the mixture.
[0037] (4) Add the calculated amount of slag to the foundation pit debris and stir evenly; then gradually add a mixed solution of solid sodium hydroxide and added water and water glass and stir until uniform, thus obtaining the foundation pit debris alkali-activated mortar.
[0038] (5) The obtained foundation pit slag alkali-activated mortar is used for emergency repair of building materials, such as standard bricks, pavement bricks, garden landscape retaining stones, curbstones, grass bricks, slope protection bricks, prefabricated drainage ditches, retaining wall blocks, etc. The repair process is similar to the traditional repair process. The remaining mortar is used to make a small cubic test block of 70.7mm*70.7mm*70.7mm to test the compressive strength, softening coefficient, and water absorption rate.
[0039] Embodiment 1:
[0040] This embodiment specifically provides a method for preparing foundation pit slag alkali-activated mortar, comprising the following steps:
[0041] (1) Take the foundation pit debris raw material, crush it to get the foundation pit debris with a particle size of less than 2.5 mm, and test the initial moisture content of the foundation pit debris to find out that it is 2%, which meets the requirements.
[0042] (2) Take 100 parts by mass of foundation pit soil, add 40 parts by mass of slag, and stir evenly for 10 minutes.
[0043] (3) Take 2 parts by mass of sodium hydroxide solid, add 50 parts by mass of water to prepare a sodium hydroxide solution, stir evenly and let stand for 10 minutes.
[0044] (4) The prepared sodium hydroxide solution in step (3) and 7 parts by mass of water glass are gradually added to the foundation pit slag and slag prepared in step (2), and stirred evenly for 5 minutes. At the same time, the fluidity of the mortar is checked. When the fluidity reaches 170 mm, stirring is stopped. At this time, the soil-binder ratio is 2.0 and the liquid-solid ratio is 0.35.
[0045] (5) The mortar obtained in step (4) is used for emergency repair of building materials products. The remaining mortar is poured into a small cubic mold of 70.7 mm*70.7 mm*70.7 mm. The compressive strength after curing for 1 day is 5.10 MPa, and the compressive strength after 28 days is 10.94 MPa, which meets the national standard M10 mortar strength requirements. The softening coefficient is 0.91 and the water absorption rate is 1.9%.
[0046] Embodiment 2:
[0047] Compared with Example 1, most of them are the same, except that the water content of the selected foundation pit slag is 2%, and the specific formula is calculated according to the soil-binder ratio = 1.0 and the liquid-solid ratio = 0.35, and the mass ratio of sodium hydroxide to slag is 1:20, and the mass ratio of sodium hydroxide to water glass is 1:3.5. The slag, sodium hydroxide solid, added water, and water glass are adjusted accordingly. The mortar obtained is used for emergency repair of building materials products, and the 28-day compressive strength of the test piece obtained by pouring the mortar surplus is 18.94MPa, which meets the requirements of M15 in the specification. The softening coefficient is 0.98 and the water absorption rate is 1.2%.
[0048] Embodiment 3:
[0049] Compared with Example 1, most of them are the same, except that the water content of the selected foundation pit slag is 2%, and the specific formula is calculated according to the soil-binder ratio = 2.0 and the liquid-solid ratio = 0.45, and the mass ratio of sodium hydroxide to slag is 1:20, and the mass ratio of sodium hydroxide to water glass is 1:3.5. The slag, sodium hydroxide solid, added water, and water glass are adjusted accordingly. The mortar obtained is used for emergency repair of building materials products, and the 28-day compressive strength of the test piece obtained by pouring the mortar surplus is 5.23MPa, which meets the requirements of M5 in the specification. The softening coefficient is 0.90 and the water absorption rate is 2.0%.
[0050] Embodiment 4:
[0051] Compared with Example 1, most of them are the same, except that the water content of the selected foundation pit slag is 2%, and the specific formula is calculated according to the soil-binder ratio = 3.0 and the liquid-solid ratio = 0.35, and the mass ratio of sodium hydroxide to slag is 1:20, and the mass ratio of sodium hydroxide to water glass is 1:3.5. The slag, sodium hydroxide solid, added water, and water glass are adjusted accordingly. The mortar obtained is used for emergency repair of building materials products. The 28-day compressive strength of the test piece obtained by pouring the mortar surplus is 5.38MPa, which meets the requirements of M5 in the specification. The softening coefficient is 0.92 and the water absorption rate is 1.8%.
[0052] Embodiment 5:
[0053] Compared with Example 1, most of them are the same, except that the water content of the selected foundation pit slag is 2%, and the specific formula is calculated according to the soil-binder ratio = 1.5 and the liquid-solid ratio = 0.30, and the mass ratio of sodium hydroxide to slag is 1:20, and the mass ratio of sodium hydroxide to water glass is 1:3. The slag, sodium hydroxide solid, added water, and water glass are adjusted accordingly. The mortar obtained is used for emergency repair of building materials products. The 28-day compressive strength of the test piece obtained by pouring the mortar surplus is 23.67MPa, which meets the requirements of M20 in the specification. The softening coefficient is 0.99 and the water absorption rate is 1.0%.
[0054] A comparative test was carried out based on Example 1, and the results are as follows:
[0055] Comparative Example 1:
[0056] Compared with Example 1, most of them are the same, except that the water content of the selected foundation pit slag is 6%, and the specific formula is calculated according to the soil-binder ratio = 4.0 and the liquid-solid ratio = 0.3, and the mass ratio of sodium hydroxide to slag is 1:20, and the mass ratio of sodium hydroxide to water glass is 1:3.5. The slag, sodium hydroxide solid, added water, and water glass are adjusted accordingly, and the 28-day compressive strength of the test piece is 3.68MPa. The softening coefficient is 0.49, and the water absorption rate is 21.3%.
[0057] Comparative Example 2:
[0058] Compared with Example 1, most of them are the same, except that the water content of the selected foundation pit slag is 6%, and the specific formula is calculated according to the soil-binder ratio = 2.0 and the liquid-solid ratio = 0.7, and the mass ratio of sodium hydroxide to slag is 1:20, and the mass ratio of sodium hydroxide to water glass is 1:3.5. The slag, sodium hydroxide solid, added water, and water glass are adjusted accordingly, and the 28-day compressive strength of the test piece is 4.71MPa. The softening coefficient is 0.69, and the water absorption rate is 18.4%
[0059] Comparative Example 3:
[0060] Compared with Example 1, most of them are the same, except that the water content of the selected foundation pit slag is 6%, and the soil-binder ratio is 4.0 and the liquid-solid ratio is 0.7, and the specific formula is calculated according to the mass ratio of sodium hydroxide to slag of 1:20 and the mass ratio of sodium hydroxide to water glass of 1:3.5. The slag, sodium hydroxide solid, added water and water glass are adjusted accordingly, and the 28-day compressive strength of the test piece is 2.11MPa. The softening coefficient is 0.23, and the water absorption rate is 34.6%
[0061] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A foundation pit slag alkali activated mortar, characterized in that: It is composed of the following raw materials in parts by mass: Foundation pit soil, 100 parts; slag, 25-80 parts; alkali activator, 5-28 parts; water, 40-80 parts; The alkaline activator is composed of 4 to 14 parts of water glass and 1 to 4 parts of sodium hydroxide.
2. The foundation pit slag alkali activated mortar according to claim 1, characterized in that: The particle size of the foundation pit slag is greater than 0 mm and less than 2.5 mm, and the moisture content is less than or equal to 4%.
3. The foundation pit slag alkali activated mortar according to claim 1, characterized in that: The particle size of the slag is greater than 0 mm and less than 0.075 mm.
4. The foundation pit slag alkali activated mortar according to claim 1, characterized in that: The water glass modulus of the water glass is 2.5-3.
5.
5. The foundation pit slag alkali activated mortar according to claim 1, characterized in that: The mass of the foundation pit soil is m1, the moisture content is w1, and the mass of the slag is m k , the mass of sodium hydroxide is m g , the mass of water glass is m y , the soil-binder ratio satisfies the following relationship:
6. The foundation pit slag alkali activated mortar according to claim 1, characterized in that: The mass of the foundation pit soil is m1, the moisture content is w1, and the mass of the added water is m s , the mass of slag is m k , the mass of sodium hydroxide is m g , the mass of water glass is m y , the liquid-to-solid ratio satisfies the following relationship:
7. The foundation pit slag alkali activated mortar according to claim 1, characterized in that: The compressive strength of the foundation pit slag alkali-activated mortar is greater than 5MPa, the softening coefficient is greater than or equal to 0.9, and the water absorption rate is less than or equal to 2%.
8. A method for preparing foundation pit slag alkali-activated mortar according to claim 1, characterized in that: The specific steps are as follows: Add slag, alkali activator and water to the foundation pit slag according to parts by mass and stir until uniform to obtain the foundation pit slag alkali activated mortar.
9. An application of the foundation pit slag alkali activated mortar according to claim 1, characterized in that: Application of the foundation pit slag alkali-activated mortar in building material products.
10. An application of the foundation pit slag alkali activated mortar according to claim 1, characterized in that: The application of the foundation pit slag alkali-activated mortar in emergency repair building material product engineering.
Citation Information
Patent Citations
Geopolymer and preparation method and application thereof
CN108046669A
High-strength muck unfired product and preparation method thereof
CN110510966A
Water-containing undisturbed shield muck baking-free building material and preparation method thereof
CN111393117A
Shield slag slurry alkali-activated regenerated mortar as well as preparation method and application thereof
CN115215597A